2011
DOI: 10.1063/1.3593012
|View full text |Cite
|
Sign up to set email alerts
|

The nature of electron lone pairs in BiVO4

Abstract: The electronic structure of BiVO4 has been studied by x-ray photoelectron, x-ray absorption, and x-ray emission spectroscopies, in comparison with density functional theory calculations. Our results confirm both the direct band gap of 2.48 eV and that the Bi 6s electrons hybridize with O 2p to form antibonding “lone pair” states at the top of the valence band. The results highlight the suitability of combining s2 and d0 cations to produce photoactive ternary oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 18 publications
23
94
0
Order By: Relevance
“…We experimentally confirm the presence of a Bi 6s -O 2p bonding state just below the valence band, consistent with other lone-pair active Bi 3+ containing metal oxides. [8,12] Excellent agreement is observed between our experimental spectra and the O 2p PDOS calculated within DFT. Our results are consistent with a revised lone pairs description, [9] whereby the combination of the low lying Bi 6p orbital (due to scalar relativistic effects) and the chemical interaction between the Bi 6s and O 2p results in the formation of electron lone pairs facilitated by a structural distortion enabling mixing between the Bi 6p and Bi 6s -O 2p states.…”
Section: +supporting
confidence: 67%
See 2 more Smart Citations
“…We experimentally confirm the presence of a Bi 6s -O 2p bonding state just below the valence band, consistent with other lone-pair active Bi 3+ containing metal oxides. [8,12] Excellent agreement is observed between our experimental spectra and the O 2p PDOS calculated within DFT. Our results are consistent with a revised lone pairs description, [9] whereby the combination of the low lying Bi 6p orbital (due to scalar relativistic effects) and the chemical interaction between the Bi 6s and O 2p results in the formation of electron lone pairs facilitated by a structural distortion enabling mixing between the Bi 6p and Bi 6s -O 2p states.…”
Section: +supporting
confidence: 67%
“…In the case of clinobisvanite BiVO 4 (Bi 3+ ), the filled Bi 6s -O 2p AB state at the VBM [12] resulted in improved p-type conductivity (by providing shallow acceptor levels, [13] and a reduced hole effective mass [14]) with a reduced band gap compared to other polymorphs with-out lone pair distortions. [15] By analogy, the peusdoclosed-shell 6s…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…1 (a)). 14,15 This heavy O 2p character offers resistance to oxidation and large over-potentials. 16 Bi 3+ 6s electron lone pairs interact with O 2p states, forming antibonding states at the top of the VB.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22] It has also been reported that the photoelectrochemical reactivity of BiVO4 can be strongly modulated by the exposed crystal facet. 23 We have recently reported a rate law analysis of the kinetics of water oxidation on hematite photoanodes as a function of the density of surface accumulated valence band holes.…”
Section: Toc Graphicsmentioning
confidence: 99%